Stepwise Induction of Inner Ear Hair Cells From Mouse Embryonic Fibroblasts via Mesenchymal- to-Epithelial Transition and Formation of Otic Epithelial Cells - Yang, Qiong; Shi, Haosong; Quan, Yizhou; Chen, Qianqian; Li, Wang; Wang, Li; Wang, Yonghui; Ji, Zhongzhong; Yin, Shan-Kai; Shi, Hai-Bo; Xu, Huiming; Gao, Wei-Qiang (Frontiers in Cell and Developmental Biology, 2021)
Although embryonic stem cells or induced pluripotent stem cells are able to differentiate into inner ear hair cells (HCs), they have drawbacks limiting their clinical application, including a potential risk of tumourigenicity. Direct reprogramming of fibroblasts to inner ear HCs could offer an alternative solution to this problem. Here, we present a stepwise guidance protocol to induce mouse embryonic fibroblasts to differentiate into inner ear hair cell-like cells (HCLs) via mesenchymal-to-epithelial transition and then acquisition of otic sensory epithelial cell traits by overexpression of three key transcription factors. These induced HCLs express multiple HC-specific proteins, display protrusions reminiscent of ciliary bundle structures, respond to voltage stimulation, form functional mechanotransduction channels and exhibit a transcriptional profile of HC signature. Together, our work provides a robust method to produce functional HCLs in vitro, which may have important implications for studies of HC development, drug discovery, and cell replacement therapy for hearing loss.